EVALUASI KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU PENDIDIKAN AGAMA KATOLIK BERBASIS MODEL KIRKPATRICK - Johannes Sohirimon Lumbanbatu; Manik, Anggi br (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of evaluating the pedagogical and professional competencies of Catholic Religious Education (PAK) teachers in improving learning quality. The research aims to analyze the effectiveness of teacher competencies based on the Kirkpatrick Model, which includes four evaluation levels: reaction, learning, behavior, and result. This study employs a qualitative approach with an evaluation research design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. Data validity was ensured through technique and source triangulation. The findings reveal that at the reaction level, students showed positive responses toward interactive and contextual learning. At the learning level, teachers demonstrated the ability to design instruction based on students’ needs through diagnostic assessment. At the behavior level, teachers consistently applied adaptive, inclusive, and student-centered teaching strategies. At the result level, there was an observable improvement in student engagement and understanding. The discussion indicates that the pedagogical and professional competencies of PAK teachers are effectively implemented, although further enhancement is needed in instructional innovation and process-based assessment optimization.